The Gunslinger: The Dark Tower I - Book 1 - King, Stephen, 1947- (New York : Scribner, 2017)
Roland, the world's last gunslinger, tracks an enigmatic Man in Black toward a forbidding dark tower, fighting forces both mortal and other-worldly on his quest.
Keywords: Roland (Fictitious character : King) -- Fiction; Gunfighters -- Fiction; Good and evil -- Fiction; Fantasy fiction